Cell-mediated immunity in rheumatoid arthritis. Issue 1 (February 1977) - Andrianakos, A A; Sharp, J T; Person, D A; Lidsky, M D; Duffy, J
Abstract : Cell-mediated immunity in rheumatoid arthritis (RA) was assessed by skin testing with six antigens in 107 patients, 94 of whom were age, sex, and race-matched with healthy individuals or patients with diseases unrelated to immunological abnormalities. 20% of RA patients were anergic. Impaired cell-mediated immunity in the RA patients was manifested by a decrease in the magnitude of skin reactivity as well as a decrease in the incidence of positive reactions to multiple antigens. Depression in cell-mediated immunity was related to age but not to sex, duration of disease, or disease activity. A slight correlation was found between absolute peripheral lymphocyte counts and the number of positive skin tests, and was confirmed by finding an association between lymphocyte counts and the size of skin reactions. A correlation was also found between lymphocyte counts and disease activity. Four explanations of the observed depression in cell-mediated immunity in RA were considered: (1) a preoccupation of the immune mechanism of the host with cell-mediated immunity reactions related to the pathogenesis of the disease; (2) a depression of cell-mediated immune reactivity by a virus infection; (3) depression of cell-mediated immunity by therapy; and (4) immune complex suppression of cell-mediated immunity. No effect of gold therapy was found. The near universal use of salicylates or other anti-inflammatory drugs did not permit investigation of the effect of these drugs on cell-mediated immunity.